Myristate induces mitochondrial fragmentation and cardiomyocyte hypertrophy through mitochondrial E3 ubiquitin ligase MUL1 - Vásquez-Trincado, César; Navarro-Márquez, Mario; Morales, Pablo E.; Westermeier, Francisco; Chiong, Mario; Parra, Valentina; Espinosa, Alejandra; Lavandero, Sergio (Frontiers in Cell and Developmental Biology, 2023)
Introduction: Cardiovascular diseases, especially metabolic-related disorders, are progressively growing worldwide due to high-fat-containing foods, which promote a deleterious response at the cellular level, termed lipotoxicity, or lipotoxic stress. At the cardiac level, saturated fatty acids have been directly associated with cardiomyocyte lipotoxicity through various pathological mechanisms involving mitochondrial dysfunction, oxidative stress, and ceramide production, among others. However, integrative regulators connecting saturated fatty acid-derived lipotoxic stress to mitochondrial and cardiomyocyte dysfunction remain elusive. Methods: Here, we worked with a cardiomyocyte lipotoxicity model, which uses the saturated fatty acid myristate, which promotes cardiomyocyte hypertrophy and insulin desensitization. Results: Using this model, we detected an increase in the mitochondrial E3 ubiquitin ligase, MUL1, a mitochondrial protein involved in the regulation of growth factor signaling, cell death, and, notably, mitochondrial dynamics. In this context, myristate increased MUL1 levels and induced mitochondrial fragmentation, associated with the decrease of the mitochondrial fusion protein MFN2, and with the increase of the mitochondrial fission protein DRP1, two targets of MUL1. Silencing of MUL1 prevented myristate-induced mitochondrial fragmentation and cardiomyocyte hypertrophy. Discussion: These data establish a novel connection between cardiomyocytes and lipotoxic stress, characterized by hypertrophy and fragmentation of the mitochondrial network, and an increase of the mitochondrial E3 ubiquitin ligase MUL1.